Elevated Levels of Serum Vascular Endothelial Growth Factor-A Are Not Related to NK Cell Parameters in Recurrent IVF Failure - R Bansal; B Ford; S Bhaskaran; M Thum; A Bansal (JRI, 2017)
Background: Vascular Endothelial Growth Factor and NK cells have an inter-related role in angiogenesis that is critical for placentation and success of in vitro fertilization. An attempt was made to assess a possible relationship between the two in this study. Methods: A case control study was performed comparing the serum levels of VEGF-A and its receptor VEGF-R1 with levels of NK cells, activated NK cells and NK cytotoxicity in 62 women with Repeated Implantation Failure (RIF). The healthy control group consisted of 72 women of similar age, without known issues in achieving pregnancy or evidence of autoimmunity. Levels of VEGF-A and VEGF-R1 were quantified by ELISA methods with standard curve interpolation. NK cell subsets were determined with flow cytometry using fluorescent-tagged anti-CD56, anti-CD16, anti-CD3 and anti-CD69. NK cytotoxicity was performed by incubating peripheral blood mononuclear cells and K562 cultured cells with propidium iodide, steroid, intralipid and intravenous immunoglobulin, using previously described methods. Statistical analysis involved Mann-Whitney-U and Spearman’s rank correlation testing with p-values defined as <0.05. Results: It was found that VEGF-A levels were significantly raised in women with RIF compared to healthy controls (362.9 vs. 171.6 pg/ml, p<0.0001), with no difference in VEGF-R1 levels between groups (1499 vs. 1202 pg/ml, p=0.4082). There was no correlation between VEGF-A or VEGF-R1 and the absolute levels of circulating NK cells, CD69 activated NK cells or NK cytotoxicity. Conclusion: The absence of correlation between VEGF-A or VEGF-R1 and NK cells suggests VEGF secretion and regulation is independent of NK cell activity in RIF.